Niobium Doping Enhances Charge Transport in TiO2 Nanorods. Issue 7 (10th March 2016) - Wang, Hsin‐Yi; Yang, Hongbin; Zhang, Liping; Chen, Jiazang; Liu, Bin
Abstract: The charge‐transport behavior of nanostructured titanium dioxide (TiO2 ) is of great interest because of the wide range of applications. In this work, we demonstrate a facile approach to improve electron transport in TiO2 nanorods (NRs) by introducing niobium (Nb) dopant into the lattice of TiO2 . The TiO2 ‐NRs doped with Nb were grown directly on fluorine doped tin oxide (FTO) substrates by a facile hydrothermal method and used directly as the photoanodes for water oxidation. The TiO2 nanorod electrode doped with 0.25 % of Nb showed 65 % improvement in photocurrent as compared with the pristine TiO2 nanorod electrode. Furthermore, by simply changing the light illuminating direction, the improvement of charge transport induced by Nb doping could be easily identified. Abstract : Niobium doping is shown to promote electron transport in rutile TiO2 . A TiO2 nanorod electrode doped with 0.25 % Nb showed 65 % improvement in photocurrent towards water oxidation as compared with the pristine TiO2 nanorod electrode. By changing the light illumination direction, the improvement of charge mobility induced by Nb doping in TiO2 could be easily identified.